Reciprocal Interplay Between Fibrillar Collagens and Collagen-Binding Integrins: Implications in Cancer Progression and Metastasis - Bourgot, Isabelle; Primac, Irina; Louis, Thomas; Noël, Agnès; Maquoi, Erik (Frontiers in Oncology, 2020)
Cancers are complex ecosystems composed of malignant cells embedded in an intricate microenvironment made of different non-transformed cell types and extracellular matrix (ECM) components. The tumor microenvironment is governed by constantly evolving cell-cell and cell-ECM interactions, which are now recognized as key actors in the genesis, progression and treatment of cancer lesions. The ECM is composed of a multitude of fibrous proteins, proteoglycans, and matricellular-associated proteins. This complex structure plays critical roles in cancer progression: it functions as the scaffold upon, which tissues are organized, but it also provides biochemical and biomechanical cues that direct cell growth, survival, migration, differentiation, modulate angiogenesis and immune function. Cells sense the biochemical and mechanical properties of the ECM through specialized transmembrane receptors that include integrins, discoidin domain receptors, and syndecans. Advanced stages of several carcinomas are characterized by desmoplasia, an extensive deposition of fibrillar collagens in the tumor microenvironment. This dense network of fibrillar collagen, particularly collagen type I, promotes tumor progression and metastasis, and correlates with low survival rates for cancer patients. In this review, we highlight how fibrillar collagens and their corresponding integrin receptors are modulated during cancer progression. We describe how the deposition and alignment of collagen fibers influence the tumor microenvironment and how fibrillar collagen-binding integrins expressed by cancer and stromal cells critically contribute in cancer hallmarks.